Power consumption analysis on an IoT network based on wemos: a case study - V. Kanakaris; G. A. Papakostas; D. V. Bandekas (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
On Internet of Things network (IoT), connections established among every device that connected to the Internet. An IoT uses different communication method instead to that, the Internet uses. Internet of Things (IoT) applications, use a light weight protocol Message Queue Telemetry Transport (MQTT). In this article an Internet of Things (IoT) system is presented, an advanced solution of monitoring the temperature and luminosity at different locations in a data centre of MQTT Server, measuring power consumption in 2 types of time of capturing data (every 0,5 min and every 1 min) making temperature and luminosity data visible over internet through cloud based dashboard. The quality of service (QoS) in some application is very crucial because the data collection is essential. This research focus on QoS in terms of power consumption as well as the battery life of the system. The results show that the battery life span is proportional to the QoS and the longevity of the battery and respectively the IoT network life depends on it.